Gender Analysis of Career Women in Qs. Al-Ahzab Verse 33 - Ayu Sulastri; Zhilal Fajar Firdaus (al-Afkar, Journal For Islamic Studies, 2026)
This article discusses career women with the object of study QS. Career women are women who are engaged in work or also called independent women. The issue of how Islam views career women is still a debate. Feminist scholars have an important role regarding the answer to this issue that arises in this contemporary era. The method in the research uses qualitative methods with literature study data collection techniques and then analyzed with content analysis techniques. The results of this study found that there are several opinions of scholars regarding whether or not it is permissible for women to have a career. The group that does not allow women to have a career makes QS. Al-Ahzab verse 33 as their argument. Meanwhile, feminists have different views regarding the meaning of the verse and the issue of career women.